1998
DOI: 10.1046/j.1365-263x.1998.00091.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between mothers’ gingival condition and caries experience of their 3‐year‐old children

Abstract: Mothers' gingival condition was associated with the prevalence and severity of dental caries of their children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 16 publications
2
29
1
Order By: Relevance
“…Good dental health knowledge is thought to be the antecedent of good attitudes and this in turn serves as the forerunner for good dental health behaviour. Other factors are, however, recognised as having an impact on the maternal dental health knowledge and attitudes such as cultural beliefs, social norms and pressure 2,3,7 . Many factors are also thought to impact the child’s oral health status including nutrition, oral hygiene behaviour, presence, and strain of Strep mutans and genetics 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Good dental health knowledge is thought to be the antecedent of good attitudes and this in turn serves as the forerunner for good dental health behaviour. Other factors are, however, recognised as having an impact on the maternal dental health knowledge and attitudes such as cultural beliefs, social norms and pressure 2,3,7 . Many factors are also thought to impact the child’s oral health status including nutrition, oral hygiene behaviour, presence, and strain of Strep mutans and genetics 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have focused on the impact, association and correlation of the mother’s oral health, habits, attitudes and knowledge on the child’s dental health because mothers are traditionally regarded as the main caregivers of their children. Therefore, mothers may play an important role in shaping the oral health, attitudes and behaviour of their children or wards 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…Chen [1986] found a strong positive correlation between mothers' preventive behavior and that of their children, suggesting a modeling effect. Other studies have identified an association between mothers' tooth brushing habits [Mattila et al, 2000;Mohebbi et al, 2008], mothers' gingival condition [Sasahara et al, 1998] and their children's experience with dental caries. Bedos et al [2005] found that children of edentulous mothers have more caries than those of dentate mothers.…”
mentioning
confidence: 99%
“…Sarnat et al reported that the more positive the mother's attitude regarding her child, the fewer carious teeth were noted, the better the child's oral hygiene, and the more dental treatment the child received (Sarnat et al, 1984). Sasahara et al showed that mothers' oral health behavior was associated with the prevalence and severity of dental caries in their children (Sasahara et al, 1998). Okada et.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of infants and young children around the world, not only in developing countries but also in developed countries (Pitts & Palmer, 1994;Widstrom & Hiiri, 1998), are still facing this severe health problem. There have been many studies focusing on mothers'/caregivers' knowledge, attitude and practices (Kamolmatyakul & Saiong, 2007;Okada et al, 2002;Sarnat et al, 1984;Sasahara et al, 1998). Many studies have shown that good levels of attitude and knowledge did not result in good practice (Benitez et al, 1994;Kamolmatyakul & Saiong, 2007;Tinanoff et al, 1999).…”
Section: Introductionmentioning
confidence: 99%